Case Report: Long-Acting Oral Cariprazine - Dyrmishi, Emanuela; De Pieri, Marco; Ferrari, Marco; Traber, Rafael; Preve, Matteo; De Peri, Luca; Bolla, Emilio (Frontiers in Psychiatry, 2022)
Cariprazine is a third-generation antipsychotic, approved for the treatment of schizophrenia and bipolar disorder and used off-label for schizoaffective disorder and treatment-resistant depression. Cariprazine is a partial agonist at dopamine receptors D2 and D3 and serotonin receptor 5HT1A and an antagonist at serotonin receptors 5HT2B and 5HT2A. It is metabolized by CYP3A4 in desmetyl-cariprazine and didesmethyl-cariprazine, both active metabolites with a half-life of 1-2 days and 2-3 weeks, respectively. Here we show the cases of 3 outpatients diagnosed with bipolar disorder type 1 (two patients) and schizoaffective disorder (one patients) and characterized by low compliance to treatment, satisfactory cognitive and personal functioning and average disease severity to whom we administered cariprazine as a monotherapy, on a bi-weekly schedule (i.e. every 72-96 hours). We evaluated response to treatment and disease remission according to conventional definitions, using rating scales BPRS, PANSS and BDI-II. Bi-weekly treatment was set either after a disease relapse (one patient), after a sustained remission obtained with daily administration of CAR (one patient) or since our first evaluation (one patient). After 4 weeks of treatment all three patients satisfied criteria for response to treatment and remission, a result that was sustained for 8 (in one patients) and 12 months (in other two patients) and still ongoing. Reported results support our hypothesis that long half-lives of cariprazine and its metabolites provide an adequate therapeutic response with a bi-weekly administration. In selected patients, cariprazine administered as a “oral long-acting” seems effective in treating acute episodes of illness and in sustaining remission, combining advantages of oral and long-acting injectable antipsychotics concerning therapeutic alliance.